2021
DOI: 10.1021/acs.jpcc.1c02623
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic, Thermal, and Structural Stability of Bimetallic MIL-53 (Al1–xCrx)

Abstract: Understanding the stability of porous materials, especially metal−organic frameworks (MOFs), is central to defining their applications in gas storage, separation, and catalysis. Herein, integrating high-temperature drop combustion calorimetry as well as simultaneous thermal and in situ structural analyses, we performed a comprehensive study on the thermodynamic, thermal, and structural stabilities of MOF in air. A family of MIL-53 (Al 1−x Cr x ) with systematically tuned metal contents was intentionally chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…Eventually, the carbon layers rapidly oxidize (combustion) to CO2 between 500 and 600 °C (combustion). 69 Above 600 °C and up to 800 °C, the TG and DSC profiles are nearly featureless. We find that MXene and AlF3•3H2O complete their conversion to oxides below 700 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the carbon layers rapidly oxidize (combustion) to CO2 between 500 and 600 °C (combustion). 69 Above 600 °C and up to 800 °C, the TG and DSC profiles are nearly featureless. We find that MXene and AlF3•3H2O complete their conversion to oxides below 700 °C.…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68][69] Dropping samples from room temperature to an oxidative environment was used to measure the enthalpic response from heating to 700 °C and oxidation, ΔHox,700°C. The individual heat effects of drop oxidation calorimetry measurements are summarized in TableS1.…”
mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) continue to attract significant attention in the fields of chemistry and material science owing to their large surface areas and flexible linker configurations that enable access to a wide range of chemical and structural diversities. Advantages of MOFs arise from the tunability of their chemical and physical properties by a variety of methods . Some of the most prominent approaches include linker modifications, defect induction, metal substitution, and introduction of guests (e.g., precious metals, small molecules). Additionally, a plethora of structural configurations (MOF isomers) may be achieved by varied synthetic conditions from a single metal–ligand combination .…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the complex interplay among thermodynamic and kinetic factors that control the formation of different metal-linker variances in MOFs . With such complexities, preparation and separation of phase pure MOFs with desired properties are challenging, with synthesis (unless finetuned) often resulting in physical mixtures containing structurally different metal–ligand phases (MOF isomers). , Thus, a variety of synthetic, computational, and calorimetric studies have been devoted to studying the extent of thermodynamic control on the formation of MOFs. ,,, Earlier works by Forster et al , examined a series of reactions between Co­(OH) 2 and succinic acid (C 4 H 6 O 4 ) under aqueous conditions, and they found that higher synthetic temperatures yielded frameworks with higher densities (lower molar volumes), increased metal–ligand ratios, and reduced hydration. , Formation of denser structures was promoted by the release of structurally confined water to the aqueous surroundings, suggesting that assemblies of dense frameworks are favored by a net entropic gain of the system . A later study by Wharmby et al examined the contributions of inherent entropy to MOF stability by monitoring the temperature-dependent structural condensation of the ZIF-4 (Zn-imidazolate, Zn­(Im 2 )) framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation